Rancang Bangun Sistem Identifikasi Nomor Kendaraan pada Gerbang Tol menggunakan Metode Pengolahan Citra - Ratna Suryawati M; Moh. Abdullah Anshori; Martono Dwi Atmadja (Politeknik Negeri Malang, 2021)
The toll ticket payment mechanism still uses e-toll cards by attaching e-toll cards to the reader at the toll gate. This has several drawbacks, including the driver having difficulty sticking the cards. At present, a device has emerged to access the toll road without attaching a card known as the OBU. However, this device has a pretty expensive price. Therefore, an access system in and out of toll roads is made without using a card. With this system, users only need to register license plates in a database and there are applications that will also be used for payment, and as trip monitoring. By using ultrasonic sensors and image processing methods, vehicle license plates that will enter the toll road can be detected. The test results are known to distance of the camera to the number plate to read correctly as far as 2 - 3 meter and when the distance of the camera to the number plate as far as 4 m, shows the wrong reading of the license plate. Ultrasonic sensor testing showed no failure in ten attempts. Ultrasonic sensors are used to detect the presence of objects vehicles when vehicles enter or exit the toll road